Control of daylight and artefacts display and placement in historic museum galleries / Noraini Ahmad - Ahmad, Noraini (Institute of Graduate Studies, UiTM, 2014)
Daylighting in historic museum galleries is not an easy criterion to manage as natural light fluctuates according to the sky conditions; hence the need for strategic daylight control programme becomes evident. Currently, there is limited information on daylight performance for conservation of artefacts in daylit historic museums in Malaysia. This thesis aims to evaluate daylight performance for artefact conservation through passive design and control strategies in historic museums under the tropical sky conditions. This research focuses on evaluating the existing illuminance levels, UV levels, daylight factor, light-fastness survey and visitors’ perception on the exhibits’ conditions and their visual responses on the daylighting conditions.